Evaluation of the Potential of Enterprises to the Implementation of Innovative Actavities in the Context of Search for Effective Funding Sourses (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The technique of the analysis of potential of the enterprise to implementation of innovative activity within partial potentials (production, innovative, financial and investment, intellectual and personnel) is developed in the paper. The algorithm for the implementation of evaluation techniques is elaborated and indicators within each potential are selected. Indicators of production capacity will give the opportunity to evaluate the total efficiency of an enterprise, its profitability, efficiency of products, the level of use of production volume. Analysis of these data will give an opportunity to see how confident the company feels as an effective manufacturer of products and whether it has unused reserves that can be used in the work. Indicators of financial and investment potential will show the stability and presence of financial opportunities for financing and innovation, because the implementation of innovations at the enterprise with unsatisfactory financial and economic indicators are unreasonably risky, not to mention the lack of resources for this. Indicators of intellectual and personnel potential will give an idea of the number and level of qualification of personnel, the level of education of employees and the presence of people with a scientific degree among them. The indicators of the innovative potential will give reason to conclude, how innovative a company is; what is the share of innovative products in total sales; what are the amounts of financing of innovative projects. Information on the firm’s innovation activities (or lack thereof) will be an important source of decision-making on the implementation of an innovation.The expediency of use of the specified system of evaluaton is justified. The share of partial potentials in the consolidated evaluation of the enterprise potential for innovation is determined. Systematization of sources of financing of innovative activity is carried out and recommendations on effective use of own and attracted financial resources taking into account the level of potential of the enterprise to introduction of innovations are developed.
Keywords: financing of innovative activity, sources of financing of innovative activity, potential of the enterprise to implementation of innovations, investments